2016
DOI: 10.1021/acs.analchem.5b03745
|View full text |Cite
|
Sign up to set email alerts
|

Fully Enzymatic Membraneless Glucose|Oxygen Fuel Cell That Provides 0.275 mA cm–2 in 5 mM Glucose, Operates in Human Physiological Solutions, and Powers Transmission of Sensing Data

Abstract: Coimmobilization of pyranose dehydrogenase as an enzyme catalyst, osmium redox polymers [Os(4,4'-dimethoxy-2,2'-bipyridine)2(poly(vinylimidazole))10Cl](+) or [Os(4,4'-dimethyl-2,2'-bipyridine)2(poly(vinylimidazole))10Cl](+) as mediators, and carbon nanotube conductive scaffolds in films on graphite electrodes provides enzyme electrodes for glucose oxidation. The recombinant enzyme and a deglycosylated form, both expressed in Pichia pastoris, are investigated and compared as biocatalysts for glucose oxidation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 48 publications
1
30
1
Order By: Relevance
“…In presence of 5.4 mM glucose, Ó Conghaile et al reached 73 77 mW cm À 2 at 0.3 V (Conghaile et al, 2016). At 4.6 mM glucose concentration we could reach a power density 21 times higher at 0.47 V (59 mW cm À 2 vs. 2.8 mW cm À 2 ) than what was reported by Nien et al (Wang et al, 2012).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In presence of 5.4 mM glucose, Ó Conghaile et al reached 73 77 mW cm À 2 at 0.3 V (Conghaile et al, 2016). At 4.6 mM glucose concentration we could reach a power density 21 times higher at 0.47 V (59 mW cm À 2 vs. 2.8 mW cm À 2 ) than what was reported by Nien et al (Wang et al, 2012).…”
Section: Discussioncontrasting
confidence: 41%
“…(Milton et al, 2015) The maximum power densities were respectively 145.7 mW cm À 2 at 0.35 V in PBS and 68.1 mW cm À 2 at 0.38 V in blood, indicating the good selectivity of our system since only ∼50% of power density is lost in blood. In a recent study, it was shown that the power density in blood could be a quarter of that observed in PBS (Conghaile et al, 2016).…”
Section: Characterization Of the Biofuel Cells In Buffer And In Humanmentioning
confidence: 92%
“…Moreover, as shown in Table 2, the cell properties of GBFC I are superior to those of GBFC II. These findings reveal that meso-NiCo 2 O 4 displays better catalytic properties to glucose than previous reports including the non-and enzyme fuel cells [48,49]. In short, the meso-NiCo 2 O 4 with large specific surface area is a promising anode material for the practical fabrication of GBFC.…”
Section: Test Of the Non-enzymatic Fuel Cellsmentioning
confidence: 54%
“…So, the only feasible analytical application of (bio)sensing without external power supply is the amperometry in short‐circuit regime. In such a regime the operation of the working electrode generally occurs far from its optimal potential due to large potential difference between the electrodes destined to maximize power output . To overcome this disadvantage of the conventional self‐powering approach, we suggest short‐circuiting the electrodes with the lowest potential difference.…”
Section: Figurementioning
confidence: 99%